Conjugation of RNA via 2′-OH acylation: Mechanisms determining nucleotide reactivity. Issue 22 (28th February 2022) - Jash, Biswarup; Kool, Eric T.
Abstract : Kinetics experiments reveal the importance of steric and inductive effects in RNA acylation. Abstract : The acylation reactivity of RNA 2′-OH groups has proven broadly useful for labeling and mapping RNA. Here we perform kinetics studies to test the mechanisms governing this reaction, and we find strong steric and inductive effects modulating reactivity. The results shed light on new strategies for improved conjugation and mapping.